Integrated marketing communication : A study of selected Malaysian public and private institutions of higher education - Siti Aishah Chu, Abdullah; Mohamad, Md Yussoff (2015)
Integrated marketing communication (IMC) is efficient in adding value to the management strategies by sending clear and consistent messages about an institution in every contact point, thereby, enabling the improvement of institutions of higher education's (IHEs') reputation. Therefore, the purpose of this study was to ascertain the strategic processes of IMC and their relevance to the Malaysian IHEs. The method of quantitative analysis was used to observe the level of IMC implementation, barriers in implementing IMC strategy and leadership styles in the selected Malaysian IHEs. The IMC four-stage framework and six components of transformational leadership theory served as the basis of the study. The study found that all four administrators of the selected Malaysian IHEs claimed that their institution have implemented all four stages of the IMC framework (100.0%), whereas none of the four educators of the selected Malaysian IHEs claimed that their institution have implemented all four stages of the IMC framework (0.0%). The lack of budget (28.57%) and functional silo (28.57%) appear to be the main barriers concerning IMC implementation in their institution. The leadership style in the selected Malaysian IHEs was interpreted by at least one transformational leadership component (62.5%). In overview, leadership that supports an open system is required in the selected Malaysian IHEs in order to support open and honest communication policies, whereby every employee is able to communicate between them and customers to convey a message on their institution which will then be oriented towards a "one -voice" communication.